New Headway : Pre-Intermediate : Workbook With Key - Soars, John ; Soars, Liz and Wheeldon, Sylvia (Oxford, New York Oxford University Press, 2015)
The world's best-selling English course - a perfectly-balanced syllabus with a strong grammar focus, and full support for students and teachers
Include Illustration
Keywords: English language -- English language--Pronunciation -- English language--Study and teaching--Foreign speakers